Castleman’s Disease, a Case report - Reddy, Ranga (Mashhad University of Medical Sciences, 2011)
INTRODUCTION: Castleman's disease is a rare lymphoproliferative disorder which may be confused with other causes of lymphadenopathy. CASE REPORT: Here we report a case of unicentric Castleman's disease presenting with cervical lymphadenopathy. The patient was treated with complete surgical excision of lesion and was disease free at the time of reporting this article. This case has been reported for its rarity. CONCLUSION: Though castleman’s disease is a relatively rare entity it should be strongly considered in the differential diagnosis of cervical lymphadenopathy.